Preparing for Parenthood; Parenting Training Module on six Child Development Aspect in East Jakarta - Akmal, Yenina; Hikmah; Astari; Hardono, Ichtineza Halida (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
The age period of 0-8 years is the most important moment for every human being to develop all the developmental features supported by parents at home and teachers / tutors at the Early Childhood Education Institute (ECE). In parenting, six main aspects must be known and applied by each parent. Lack of education, nutritional knowledge, care and care, and aspects of clean-living habits in the family can have an impact on children's growth and development processes. This study aims to develop a module 6 aspects of child development for parental guidance. This study uses a research and development approach to test the effectiveness of the posttest design. Respondents in this study are parents who have children up to 5 years and early childhood educators. The findings show that from these six main aspects, it seems that parents and ECE tutors do not yet understand the ECE concept. In another perspective, there is still a lack of knowledge about these 6 main aspects which require training and parenting modules to develop the 6 aspects of child development. Keywords: Early Childhood Education, Child Development Aspect, Parenting Training Module References: Arikunto, S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: Asdi Mahasatya. Britto, P. R., Lye, S. J., Proulx, K., Yousafzai, A. K., Matthews, S. G., Vaivada, T., … Bhutta, Z. A. (2017). Nurturing care: promoting early childhood development. The Lancet, 389(10064), 91–102. https://doi.org/10.1016/S0140-6736(16)31390-3 Coore Desai, C., Reece, J. A., & Shakespeare-Pellington, S. (2017). The prevention of violence in childhood through parenting programmes: a global review. Psychology, Health and Medicine, 22(February), 166–186. https://doi.org/10.1080/13548506.2016.1271952 Darling-Churchill, K. E., & Lippman, L. (2016). Early childhood social and emotional development: Advancing the field of measurement. Journal of Applied Developmental Psychology, 45, 1–7. https://doi.org/10.1016/j.appdev.2016.02.002 Davis, S., Votruba-Drzal, E., & Silk, J. S. (2015). Trajectories of Internalizing Symptoms From Early Childhood to Adolescence: Associations With Temperament and Parenting. Social Development, 24(3), 501–520. https://doi.org/10.1111/sode.12105 Đorđić, V., Tubić, T., & Jakšić, D. (2016). The Relationship between Physical, Motor, and Intellectual Development of Preschool Children. Procedia - Social and Behavioral Sciences, 233(May), 3–7. https://doi.org/10.1016/j.sbspro.2016.10.114 Eisenberg, N., Taylor, Z. E., Widaman, K. F., & Spinrad, T. L. (2015). Externalizing symptoms, effortful control, and intrusive parenting: A test of bidirectional longitudinal relations during early childhood. Development and Psychopathology, 27(4), 953–968. https://doi.org/10.1017/S0954579415000620 Gall, M. D., Gall, J. P., & Borg, W. R. (2007). Educational Research: An Introduction (4th ed.). New York: Longman Inc. Gardner, F., Montgomery, P., & Knerr, W. (2016). Transporting Evidence-Based Parenting Programs for Child Problem Behavior (Age 3–10) Between Countries: Systematic Review and Meta-Analysis. Journal of Clinical Child and Adolescent Psychology, 45(6), 749–762. https://doi.org/10.1080/15374416.2015.1015134 Gilmer, C., Buchan, J. L., Letourneau, N., Bennett, C. T., Shanker, S. G., Fenwick, A., & Smith-Chant, B. (2016). Parent education interventions designed to support the transition to parenthood: A realist review. International Journal of Nursing Studies, 59, 118–133. https://doi.org/10.1016/j.ijnurstu.2016.03.015 Grindal, T., Bowne, J. B., Yoshikawa, H., Schindler, H. S., Duncan, G. J., Magnuson, K., & Shonkoff, J. P. (2016a). The added impact of parenting education in early childhood education programs: A meta-analysis. Children and Youth Services Review, 70, 238–249. https://doi.org/10.1016/j.childyouth.2016.09.018 Guyer, A. E., Jarcho, J. M., Pérez-Edgar, K., Degnan, K. A., Pine, D. S., Fox, N. A., & Nelson, E. E. (2015). Temperament and Parenting Styles in Early Childhood Differentially Influence Neural Response to Peer Evaluation in Adolescence. Journal of Abnormal Child Psychology, 43(5), 863–874. https://doi.org/10.1007/s10802-015-9973-2 Jones, D. E., Feinberg, M. E., Hostetler, M. L., Roettger, M. E., Paul, I. M., & Ehrenthal, D. B. (2018). Family and Child Outcomes 2 Years After a Transition to Parenthood Intervention. Family Relations, 67(2), 270–286. https://doi.org/10.1111/fare.12309 Jürges, H., Schwarz, A., Cahan, S., & Abdeen, Z. (2019). Child mental health and cognitive development: evidence from the West Bank. Empirica, 46(3), 423–442. https://doi.org/10.1007/s10663-019-09438-5 Kalland, M., Fagerlund, Å., Von Koskull, M., & Pajulo, M. (2016). Families First: The development of a new mentalization-based group intervention for first-Time parents to promote child development and family health. Primary Health Care Research and Development, 17(1), 3–17. https://doi.org/10.1017/S146342361500016X Knauer, H. A., Ozer, E. J., Dow, W. H., & Fernald, L. C. H. (2019). Parenting quality at two developmental periods in early childhood and their association with child development. Early Childhood Research Quarterly, 47, 396–404. https://doi.org/10.1016/j.ecresq.2018.08.009 Kopala-Sibley, D. C., Cyr, M., Finsaas, M. C., Orawe, J., Huang, A., Tottenham, N., & Klein, D. N. (2018). Early Childhood Parenting Predicts Late Childhood Brain Functional Connectivity During Emotion Perception and Reward Processing. Child Development, 00(0), 1–19. https://doi.org/10.1111/cdev.13126 Kurniah, N., Andreswari, D., & Kusumah, R. G. T. (2019). Achievement of Development on Early Childhood Based on National Education Standard. 295(ICETeP 2018), 351–354. https://doi.org/10.2991/icetep-18.2019.82 Leijten, P., Raaijmakers, M. A. J., Orobio de Castro, B., van den Ban, E., & Matthys, W. (2017). Effectiveness of the Incredible Years Parenting Program for Families with Socioeconomically Disadvantaged and Ethnic Minority Backgrounds. Journal of Clinical Child and Adolescent Psychology, 46(1), 59–73. https://doi.org/10.1080/15374416.2015.1038823 Lomanowska, A. M., Boivin, M., Hertzman, C., & Fleming, A. S. (2017). Parenting begets parenting: A neurobiological perspective on early adversity and the transmission of parenting styles across generations. Neuroscience, 342, 120–139. https://doi.org/10.1016/j.neuroscience.2015.09.029 Lucassen, N., Kok, R., Bakermans-Kranenburg, M. J., Van Ijzendoorn, M. H., Jaddoe, V. W. V., Hofman, A., … Tiemeier, H. (2015). Executive functions in early childhood: The role of maternal and paternal parenting practices. British Journal of Developmental Psychology, 33(4), 489–505. https://doi.org/10.1111/bjdp.12112 Molchanov, S. V. (2013). The Moral Development in Childhood. Procedia - Social and Behavioral Sciences, 86, 615–620. https://doi.org/10.1016/j.sbspro.2013.08.623 Morris, A. S., & Williamson, A. C. (2019). Building early social and emotional relationships with infants and toddlers: Integrating research and practice. Building Early Social and Emotional Relationships with Infants and Toddlers: Integrating Research and Practice, 1–351. https://doi.org/10.1007/978-3-030-03110-7 Parhomenko, K. (2014). Diagnostic Methods of Socio – Emotional Competence in Children. Procedia - Social and Behavioral Sciences, 146, 329–333. https://doi.org/10.1016/j.sbspro.2014.08.142 Rutherford, H. J. V., Wallace, N. S., Laurent, H. K., & Mayes, L. C. (2015). Emotion regulation in parenthood. Developmental Review, 36, 1–14. https://doi.org/10.1016/j.dr.2014.12.008 Sheedy, A., & Gambrel, L. E. (2019). Coparenting Negotiation During the Transition to Parenthood: A Qualitative Study of Couples’ Experiences as New Parents. American Journal of Family Therapy, 47(2), 67–86. https://doi.org/10.1080/01926187.2019.1586593 Sitnick, S. L., Shaw, D. S., Gill, A., Dishion, T., Winter, C., Waller, R., … Wilson, M. (2015). Parenting and the Family Check-Up: Changes in Observed Parent-Child Interaction Following Early Childhood Intervention. Journal of Clinical Child and Adolescent Psychology, 44(6), 970–984. https://doi.org/10.1080/15374416.2014.940623 Sulik, M. J., Blair, C., Mills-Koonce, R., Berry, D., & Greenberg, M. (2015). Early Parenting and the Development of Externalizing Behavior Problems: Longitudinal Mediation Through Children’s Executive Function. Child Development, 86(5), 1588–1603. https://doi.org/10.1111/cdev.12386 Theise, R., Huang, K. Y., Kamboukos, D., Doctoroff, G. L., Dawson-McClure, S., Palamar, J. J., & Brotman, L. M. (2014). Moderators of Intervention Effects on Parenting Practices in a Randomized Controlled Trial in Early Childhood. Journal of Clinical Child and Adolescent Psychology, 43(3), 501–509. https://doi.org/10.1080/15374416.2013.833095 UNDP. (2018). Human Development Indices and Indicators. 2018 Statistical Update. United Nations Development Programme, 27(4), 123. Retrieved from http://hdr.undp.org/sites/default/files/2018_human_development_statistical_update.pdf%0Ahttp://www.hdr.undp.org/sites/default/files/2018_human_development_statistical_update.pdf%0Ahttp://hdr.undp.org/en/2018-update